O8 Virtual sim- remote 360° simulation and debrief. (10th November 2020) - Mason, Timothy; Peres, Nick
Abstract : Simulation is resource heavy in terms of time, space, equipment, and faculty, with limitations on the number of people you can deliver each session to. During the COVID-19 pandemic, social distancing makes face to face simulation more challenging. After working with a local healthcare VR team through a return to training project, 1 we explored benefits and acceptability of remotely debriefing 360° videos of simulated paediatric emergencies. Remote debrief has been used successfully in the past to train teams 2 and faculty. 3 However, it's use in the context of 360 content is still novel. The theory being that because the participant is an 'active observer' this would bring a more immersive experience. Summary of Educational Project: Using 360° content filmed at RD&E hospitals, we ran remote virtual simulation sessions over MS Teams video conferencing platform in local and regional paediatric teaching sessions. We asked the learners to watch a scenario (eg; https://youtu.be/KpQl0VUfERI), from which we guided them to interact with the video, directing their view in the 360° media to whatever interested them. This was followed with a debrief following a standard structure. We then collected feedback on its acceptability & similarity to face to face simulation. Summary of Results: April 2020 – July 2020. 6 Sessions at least 66 learners, 38 gave feedback. 4 different 360 scenarios used. Used for local, regional (South-West) and international (Wales) teaching. Levels ranged from medical students to Paediatric consultants. Most Common device used: computers or smartphone. Location accessed: Work and Home. Feedback was globally positive 100% 'would use it again', average rating of 8.3/10 (10= Loved it, 1=Hated). Feedback was rich and promising: 'more life-like than expected' 'safer than real sim as I didn't feel judged' '360 element meant you had a different perspective'. N.B We had more senior grade learners than our usual simulation sessions – this directed debriefs towards the non-technical learning which was discussed more than the medical learning. Additional positives include; - easy accessibility for anyone to view 360 video (no need beyond normal consumer technology) - no need for additional faculty - relatively quick and engaging to run remotely. The experiences have established 'best practises' for this modality. Conclusion: We recommend remote 360 sim with debrief as a fantastic adjunct to standard simulation. The modality is well received and a safe method of providing people with an experience of emergency scenarios which is improved though debrief. References: Mason T G627(P) Is virtual resus training the future? Can 360 degree 'immersive video' engage paediatric trainees safely in life support training? – A project as part of the south west return to paediatric training course (SWRPT). Archives of Disease in Childhood 2019;104:A254. Meaklim A. Remote debriefing - A new paradigm for low resource and rural hospitals?. 2016;31:59–62. Gross IT, Whitfill T, Auzina L, et al. Telementoring for remote simulation instructor training and faculty development using telesimulation BMJ Simulation and Technology Enhanced LearningPublished Online First: 18 May 2020. doi: 10.1136/bmjstel-2019-000512